Factors influencing common diagnoses made during first-opinion small-animal consultations in the United Kingdom - Robinson, N.J.; Dean, Rachel S.; Cobb, M.; Brennan, Marnie L. (Elsevier, 2016)
It is currently unclear how frequently a diagnosis is made during small-animal consultations or how much of a role making a diagnosis plays in veterinary decision-making. Understanding more about the diagnostic process will help direct future research towards areas relevant to practicing veterinary surgeons. The aim of this study was to determine the frequency with which a diagnosis was made, classify the types of diagnosis made (and the factors influencing these) and determine which specific diagnoses were made for health problems discussed during small-animal consultations.